1995
DOI: 10.3109/10408369509082592
|View full text |Cite
|
Sign up to set email alerts
|

Hantaviruses: Clinical, Microbiologic, and Epidemiologic Aspects

Abstract: Hantaviruses comprise a genus of the family Bunyaviridae. Bunyaviruses are enveloped viruses with a negative-sense, tripartite RNA genome. Hantaviruses are etiologic agents for two acute and severe illnesses of man, hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS). Each hantavirus is primarily associated with a single rodent host species or genus, and is transmitted to man through accidental inhalation or ingestion of virus-contaminated rodent excreta. The distribution of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 112 publications
1
42
0
1
Order By: Relevance
“…The only autochthonous New-World hantavirus recognized prior to 1993 was Prospect Hill virus, associated with the meadow vole (Microtus pennsylvanicus). 15 Recently, Bloodland Lake virus was described from the prairie vole, 25 and Isla Vista virus from the California vole (M. californicus), 4 and a genetically distinct hantavirus has been described from M. montanus. 26 No distinct hantavirus has been described from the red-backed vole.…”
Section: Discussionmentioning
confidence: 99%
“…The only autochthonous New-World hantavirus recognized prior to 1993 was Prospect Hill virus, associated with the meadow vole (Microtus pennsylvanicus). 15 Recently, Bloodland Lake virus was described from the prairie vole, 25 and Isla Vista virus from the California vole (M. californicus), 4 and a genetically distinct hantavirus has been described from M. montanus. 26 No distinct hantavirus has been described from the red-backed vole.…”
Section: Discussionmentioning
confidence: 99%
“…This region is dotted with numerous rural municipalities dedicated principally to agriculture; in comparison, the central area is typically urban, and the north-western area combines both urban and rural municipalities, with cattle-raising being an important activity. In general, hantavirus infection affects rural populations more than urban ones [1].…”
Section: Serological Study Of Human Hantavirus Infection 863mentioning
confidence: 99%
“…There are numerous species of hantaviruses that may cause disease in man. Their distribution is world-wide, with particular endemic areas being south-eastern Asia, northern and eastern parts of Europe and, more recently, south-western USA [1].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers are also at risk because of increased contact with rodents and their surroundings (4,30,37,38). Crowcroft et al (39) reported that Hantavirus infection was 6.1 times more frequent in people spending more than 16 h a day in forests (OR = 1.9-19.5; P = 0.03).…”
Section: Discussionmentioning
confidence: 99%